Occurrence of grapevine Pinot gris virus in commercial table grapes in Peru - Alvarez Bernaola, Armando (2025)
In the 2022–2023 season, Peru maintained its status as the world's leading exporter of table grapes, exporting 593,000 tons comprised of more than 53 varieties. The varietal change and the increase of new producing areas has brought several phytosanitary problems, including those of viral aetiology. Since 2022, occasional grapevines in commercial vineyards in Ica (southern Peru), the main producing area in the country, have been observed with complex symptoms including short internodes, stunting and deformation of the leaves (Fig. 1) and chlorotic mottling on leaf blades (Fig. 2). At fruiting, symptoms included heterogeneity in berry development (Fig. 3), delayed ripening and consequently reduced yield.